Pemenuhan Hak Restitusi Terhadap Anak Korban Tindak Pidana Kejahatan Seksual (Studi Penelitian Pengadilan Negeri Medan Kelas I-A Khusus) - Muhammad Mitra Lubis (Fakultas Hukum universitas Islam Sumatera Utara, 2020)
AbstractRestitution is the payment of compensation which is charged to the offender based on a court decision that has permanent legal force for material and / or material losses suffered by the victim or his heir. In the PP it is stated that every child who is a victim of a criminal offense is entitled to get restitution.The problems here are: rules of restitution rights in the Indonesian legal system, judicial legal considerations in fulfilling the right of resitution to children victims of sexual crimes in the jurisdiction of the Medan Class IA Special District, application of restitution rights as well as obstacles and efforts to fulfill restitution rights against children victims of sexual crimes in Medan, especially in the jurisdiction of Medan Special Class IA PN.This research is descriptive with a normative juridical approach.